Understanding socioeconomic aspects influencing CSA adoption - Howland, Fanny C.; Andrieu, Nadine; Bonilla Findji, Osana (2018)
This working paper presents the development and piloting of a qualitative methodological approach aiming to better understand the socioeconomic factors that influence adoption of Climate-Smart Agricultural (CSA) options in smallholder farming communities. The field work was conducted in the Cauca Climate-Smart Village (CSV) located in Colombia. Two types of results are presented. First is the three-step methodology developed to answer: (1) Which CSA options promoted by CCAFS have been adopted by farmers? (2) Who within the community is adopting which CSA option(s)? What is the diversity in the types of farmers according to their CSA adoption profile? (3) What are the motivations and enabling/constraining factors for each farmer type to adopt a CSA option? Then, results show the use of this methodology made from direct CCAFS beneficiaries and non-CCAFS-related farmers. Results show that home gardens were the most commonly adopted practice, followed by compost preparation and water harvesting. Three types of farmers were identified: older larger-scale displaced adopters; middle-aged medium-scale non-displaced adopters; and smaller-scale non-adopters who perceive climate change risks and feel unprepared. The main farmers’ motivations for adopting CSA options were associated with cost saving and interest in organic production. Assets, knowledge, and agency have been key for the adoption of CSA options.